The Linguistic Errors in Commercial Signs in the Southern Region and the Capital of the Kingdom of Bahrain: A Descriptive and Analytical Study - Abouhamra, Maha Fahed; Mukhtar, Ibrahim Suliman Ahmed; Juma, Mohamed Jaafar Hasan Ali (Journal of Arabic Language Sciences and Literature, 2025)
This study aims to analyze linguistic errors in commercial signage across the Capital and Southern Governorates of the Kingdom of Bahrain during the academic year 2023–2024, within the framework of applied linguistics and through a descriptive–analytical approach. A field-based coding sheet was designed to record and classify errors in a clustered sample of 200 signs (100 from each governorate), categorized into spelling, grammar, translation, and Arabization. The findings revealed a total of 277 errors, including 157 spelling errors (56.6%), 11 grammatical errors (4%), 66 translation errors (24%), and 43 Arabization errors (15.5%). Variation was observed between regions: spelling errors were more frequent in the Capital, while grammatical, translation, and Arabization errors were more prominent in the Southern Governorate. Based on these findings, the study recommends developing a simplified national guide for signage writing, requiring linguistic proofreading before licensing and installation, and providing training programs for designers and advertising companies on functional bilingual writing. These results highlight the need for a clear linguistic policy that ensures the visibility of Arabic in commercial spaces while maintaining balance with translation needs.